Barriers to Testing and Treatment for Chagas Disease among Latino Immigrants in Georgia - Rebecca M. Minneman; Monique M. Hennink; Andrea Nicholls; Sahar S. Salek; Francisco S. Palomeque; Amina Khawja; Lauren C. Albor; Chester C. Pennock; Juan S. Leon (Journal of Parasitology Research)
Background. The lack of testing and treatment of Chagas disease (CD), caused by Trypanosoma cruzi, amongst infected immigrants in the USA increases the risk of serious health complications and transmission (congenital or via blood transfusions). Goal. Our goal was to identify the barriers to testing and treatment of CD and understand the process of seeking healthcare amongst Latino immigrants in Georgia. Methods. In this qualitative study, eleven focus group discussions were conducted with 82 Latino immigrants, including migrant farm workers. Grounded theory was used to collect and analyze the data to develop an inductive conceptual framework to explain the context and process of seeking healthcare for CD amongst this at-risk population. Results. Participants were not aware of CD. Three healthcare seeking behaviors were identified: delaying treatment, using traditional remedies, and using either mainstream or alternative health providers. Behaviors and motivations differed by gender, and the use of licensed medical providers was considered a last resort due to the cost of healthcare, loss of earnings while seeking care, and fear of diagnosis with fatal illness. Discussion. Providing free or low cost services, mobile clinics, and education regarding CD is critical to increase testing and treatment of CD in the US.